L’émigration des Canadiens français vers les États-Unis, 1790-1940 : problématique et coups de sonde - Paquet, Gilles; Smith, Wayne (L'Actualité économique, 1983)
AbstractUsing a Faucher-Dales approach to migration phenomena, the authors sketch a plausible scenario of the pattern of migration of French Canadians to the United States as regulated by the size of the differential economic rent. Making use of all available data, the authors show that this approach would appear to be vindicated to the extent that the scenario it suggests is compatible with the available estimates of the migration flows.